2008
DOI: 10.1002/humu.20771
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of maternal uniparental disomy 14 in patients with an epimutation and a deletion of the imprintedDLK1/GTL2gene cluster

Abstract: Maternal uniparental disomy 14 [upd(14)mat] is associated with a recognizable phenotype that includes pre- and postnatal growth retardation, neonatal hypotonia, feeding problems and precocious puberty. Chromosome 14 contains an imprinted gene cluster, which is regulated by a differentially methylated region (IG-DMR) between DLK1 and GTL2. Here we report on four patients with clinical features of upd(14)mat who show a maternal-only methylation pattern, but biparental inheritance for chromosome 14. In three of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 20 publications
6
62
0
1
Order By: Relevance
“…A real-time PCR assay for the promoter region of MEG3 was performed as previously described by Buiting et al 16 Multilocus methylation-specific single nucleotide primer extension (MS-SNuPE)…”
Section: Quantitative Pcr (Qpcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…A real-time PCR assay for the promoter region of MEG3 was performed as previously described by Buiting et al 16 Multilocus methylation-specific single nucleotide primer extension (MS-SNuPE)…”
Section: Quantitative Pcr (Qpcr)mentioning
confidence: 99%
“…[11][12][13] In both syndromes, three types of molecular alterations have been reported: uniparental disomy, deletions and epimutations. 7,[14][15][16][17][18][19] In contrast to uniparental disomy and epimutations, deletions affecting regulatory elements in 14q32 on the maternal or the paternal allele are associated with a highrecurrence risk. 7,19 It has been shown that both the MEG3-and the IG-DMR function as imprinting control centers in the placenta and the body.…”
Section: Introductionmentioning
confidence: 99%
“…6 Patients with maternal or paternal UPD of human chromosome 14 (UPD14; named Temple and Kagami-Ogata syndromes, respectively) present with distinct developmental abnormalities, including hydrocephalus, hypotonia, abnormal growth, mental retardation, craniofacial dismorphisms, altered puberty onset, abnormal rib cage and others. 7,8 Several genes within this region, including DLK1 and MEG3, are subject to genomic imprinting, that is, they exhibit a high degree of monoallelic expression. 6 However, it is uncertain whether DIO3 is imprinted.…”
Section: Introductionmentioning
confidence: 99%
“…1 A number of imprinting syndromes due to aberrant expression of imprinted genes have been described. These include transient neonatal diabetes (TND), Russell-Silver syndrome (RSS), BeckwithWiedemann syndrome (BWS), Prader-Willi syndrome, Angelman syndrome, Pseudohypoparathyroidism type 1b, maternal (also called Temple syndrome 2 ) and paternal UPD 14 related disorder. Though this list represents diverse phenotypes, there are common features: phenotypically, many are associated with disordered growth; molecularly, each may be caused by aberrant methylation at a differentially methylated region (DMR).…”
Section: Introductionmentioning
confidence: 99%